Peranan Kemasan Untuk Meningkatkan Pemasaran Produk Kopi Bubuk Pada SMKN 1 Agribisnis Dangau Datuk Kota Bengkulu - Afriani, Sulisti; Irwanto, Tito; Sari, Desti Rupita (Jurnal Dehasen Mengabdi, 2023)
Packaging is very closely related to the product. Attractive packaging will add to the attractiveness of the product so as to arouse consumer interest to buy it. at this time SMKN 1 Agribusiness Dangau Datuk has produced ground coffee with quite attractive packaging, but the information available on the packaging is incomplete there are several things that have not been listed in the packaging including information about food additives, composition, instructions for use, storage methods and nutritional value. This is known after community service activities are held, hopefully the input given in the future can be improved so as to increase consumer confidence to buy the product